Teichoskopie: Der (weibliche) Blick auf den Krieg - Fuhrer, Therese (Hyperboreus, 2015)
The scenes in ancient literature in which one or more individuals watch and comment on a ﬁght or battle, usually from an elevated position – e.g. the ramparts of a fortress –, present an outsiders’ perspective: the persons involved are not taking an active part in the war. However, most of them are indeed involved in the events in some way, in most cases by being related, acquainted or emotionally linked in some other way to one of the combatants. This role is usually given to women (or to individuals who cannot ﬁght, for some speciﬁc reason, because of physical weakness or on account of their profession). The paper aims to examine a series of such teichoskopia scenes within depictions of battles or ﬁghts, addressing the question of how war is ‘seen’ through this presentation of a female perspective – that is, through the internal focalisation from the viewpoint of a woman who is not a participant in the ﬁghting – and thereby perhaps commented upon critically or afﬁrmatively. Central to the discussion are epic (Iliad, Statius, Valerius Flaccus) and lyric texts (Horace).